The complete chloroplast genome and phylogenetic status of carpesium nepalense less. 1831 (asteraceae) - Yu Su; Jingyi Peng; Yining Di; Hancaiyuan Zheng; Xianhan Huang; Lufeng Liu (Mitochondrial DNA. Part B. Resources)
The complete chloroplast genome of Carpesium nepalense (Asteraceae), an important medicinal herb, was characterized. It exhibits a typical quadripartite structure with inverted repeats (24,947 bp), a large single-copy region (82,870 bp), and a small single-copy region (18,473 bp), with 37.7% GC content. The genome contains 133 genes, including 88 protein-coding, 37 tRNA, and 8 rRNA genes. Phylogenetic analysis confirms Carpesium as monophyletic, with C. nepalense genetically closest to C. cernuum, C. faberi, C. lipskyi, and C. longifolium. This work enriches the molecular database of Carpesium and provides new genomic resources for the development and utilization of medicinal herbs..